DIRK SIJMONS - Landscape and energy. Designing transition - Hazendonk, Niek (ZARCH, 2021)
Dirk SijmonsLandscape and energy. Designing transitionRotterdam: Nai010 Publishers, 2014. 480 p. Idioma: inglés. Tapa dura. 80 €ISBN: 9789462081130